INVESTIGATION OF THE RS3798220 POLYMORPHISM OF THE LIPOPROTEIN (A) GENE, LIPOPROTEIN (A) CONCENTRATION, AND THEIR ASSOCIATION WITH THE SEVERITY OF CORONARY ARTERY LESIONS IN PATIENTS WITH ACUTE CORONARY SYNDROME (Vietnam Journal of Community Medicine, 2026)
Objective: To investigate characteristics of the rs3798220 polymorphism of lipoprotein (a) gene, serum lipoprotein (a) levels, and their association with the severity of coronary artery lesions in patients with acute coronary syndrome.Subjects and methods: A cross - sectional descriptive study was conducted on 77 patients treated at Tay Ninh General Hospital and Xuyen A General Hospital - Tay Ninh from June 2025 to April 2026.Results: The median age was 63.0 years (IQR: 56.0-69.0), with males accounting for a higher proportion than females (62.3% vs. 37.7%). The TT genotype was predominant (66.2%), whereas the TC genotype accounted for 33.8%. The median lipoprotein (a) concentration was 58.0 mg/dL (IQR: 18.20-143.8). Patients with hypertension had higher lipoprotein (a) levels compared to those without hypertension, at 125.6 mg/dL (IQR: 59.4-181.5) and 39.7 mg/dL (IQR: 17.7-134.0), respectively. Multivariable logistic regression analysis demonstrated that diabetes mellitus (OR = 2.34; 95% CI: 1.10-4.82), lipoprotein (a) concentration (OR = 1.17; 95% CI: 1.02-1.34), and TC genotype (OR = 3.28; 95% CI: 1.92-5.43) were independently associated with severe coronary artery lesions (p < 0.05).Conclusion: Diabetes mellitus, elevated lipoprotein (a) levels, and TC genotype of rs3798220 polymorphism were independently associated with severe coronary artery lesions.
Keywords: Acute coronary syndrome, rs3798220 polymorphism, lipoprotein (a).